2011
DOI: 10.1172/jci57867
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral amyloid-β proteostasis is regulated by the membrane transport protein ABCC1 in mice

Abstract: In Alzheimer disease (AD), the intracerebral accumulation of amyloid-β (Aβ) peptides is a critical yet poorly understood process. Aβ clearance via the blood-brain barrier is reduced by approximately 30% in AD patients, but the underlying mechanisms remain elusive. ABC transporters have been implicated in the regulation of Aβ levels in the brain. Using a mouse model of AD in which the animals were further genetically modified to lack specific ABC transporters, here we have shown that the transporter ABCC1 has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
180
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(188 citation statements)
references
References 39 publications
6
180
2
Order By: Relevance
“…Microglial cells surrounding Aβ-plaques in APP/PS1 mice were found to phagocytose Aβ to a lesser extent than was observed in APP/PS1/Nlrp3 -/-mice. These findings add to evidence suggesting that impaired clearance of Aβ might be a crucial factor in sporadic Alzheimer disease-a view seconded at the meeting by data presented by Jens Pahnke (U. Magdeburg and DZNEMagdeburg, Germany), who showed that loss of ABC transporters B1 and C1, which extrude Aβ from the CNS parenchyma, can lead to a substantial increase in Aβ-load [24]. These transporters not only are regulated by mitochondria [25], but also have a substantial impact on cerebral regeneration [26].…”
Section: Translation Meets Systems Medicinesupporting
confidence: 72%
“…Microglial cells surrounding Aβ-plaques in APP/PS1 mice were found to phagocytose Aβ to a lesser extent than was observed in APP/PS1/Nlrp3 -/-mice. These findings add to evidence suggesting that impaired clearance of Aβ might be a crucial factor in sporadic Alzheimer disease-a view seconded at the meeting by data presented by Jens Pahnke (U. Magdeburg and DZNEMagdeburg, Germany), who showed that loss of ABC transporters B1 and C1, which extrude Aβ from the CNS parenchyma, can lead to a substantial increase in Aβ-load [24]. These transporters not only are regulated by mitochondria [25], but also have a substantial impact on cerebral regeneration [26].…”
Section: Translation Meets Systems Medicinesupporting
confidence: 72%
“…ATP-binding cassette transporters, as well as being involved in lipid metabolism, cholesterol efflux, and drug transport, are important in removing intracellular Aβ and are dysfunctional in AD; as they are ATP dependent, it has been suggested that reduced energy production could lead to a build-up of Aβ [239]. Specifically, both ABCG2 and ABCC1 have been found to be involved in Aβ transport [240,241]. Whether or not CBD may beneficially act through these transporters is difficult to gauge, as not only might they inhibit ABC-mediated transport of Aβ, but the reported IC 50 may also be too high to be relevant physiologically.…”
Section: Cbd Transporter Targets In Neurodegenerationmentioning
confidence: 99%
“…The decline of the levels of the transporter at the BBB occurs during normal aging, and is positively correlated with the accumulation of Aβ (Silverberg et al, 2010). Due the contribution of ABC transporters on Aβ clearance in AD, they have been proposed as potential therapeutic targets (Krohn et al, 2011). Moreover, ABCB1 dysfunction has been also associated with other neurodegenerative disorders such as PD, progressive supranuclear palsy (PSP) or genetically associated with depressive disorders (Bernstein et al, 2014).…”
Section: Abc Transportersmentioning
confidence: 99%